The Influence of Oriental Literature on the Formation of Romantic Literature in Europe - Gulnoz A Mamarasulova (Researchparks Publishing, 2021)
This article examines how the Arabian tales A Thousand and One Nights, which was first translated from Arabic into French, made a major turn in European literature. The romantic movements that began in France spread throughout England. The melody of Arabian tales inspired French and English writers. Their interest in the Oriental world increased and it encouraged them to explore the geography, nature, customs, traditions, historical figures, and national values of the eastern countries through other literature. As a result, writers began to compose new works in a romantic spirit. In England, in the late 18th century, the poets of the Lake School, Southey, Coleridge and Wordsworth, laid the foundations of the Romantic period in English literature with their rich oriental works.